Now hear this!: increasing purchase intentions of green products in business-to-business marketing - Justin R. Muñoz (Cogent Business & Management)
The current study analyzes if higher purchase intention can result from the communication, compliance with, and reporting of sustainable initiatives, and the perceived quality of products in a business-to-business (B2B) context. The theory of consumption values, and the triple bottom line theory help set the study’s framework. Data was gathered through a Qualtrics panel survey of 174 B2B buyers. Structural Equation Modeling was used as the methodology. Results suggest that sustainability and reporting efforts from the seller can positively impact purchase intention. The perceived quality of the products sold moderates the relationship between the seller and the buyer’s intent to purchase sustainable products. Managers should avoid creating voluntary sustainability measures. The company instead could have invested resources into enhanced communication and reporting sustainable initiative results as motivators for buyers to purchase high-quality green products. This study promotes novel discourse on sustainable communication and the perceived quality of sustainable products. As the seller appeals to a buyer in a societal context by offering environmentally friendly products, sustainability becomes central to revenue generation through the triple bottom line perspective.